Spiritual Approach as Nursing Management Strategy to Improve the Quality of Life of Palliative Patients - Gulo, Adventy Riang Bevy; Sipayung, Rosetty Rita; Lase, Yesta Ricam Fredrik (Alta Dharma Publisher, 2025)
Background: Spiritual support in nursing management plays a vital role in palliative care by improving patients’ quality of life, reducing anxiety, and enhancing emotional resilience in those with progressive, incurable conditions requiring holistic care. Objective: To assess the effectiveness of the Spiritual Management Approach in improving the quality of life of palliative patients in hospitals. Method: A quasi-experimental pre-test–post-test study was conducted on 50 respondents from two hospitals in North Sumatra, Indonesia, using simple random sampling. Data were collected through the SCCS and SF-36 questionnaires and analyzed statistically. Result: The Spiritual Management Approach significantly improved patients’ quality of life, with mean scores increasing from 1.24 to 1.44 and a significant correlation (r = 0.381; p = 0.006). Conclusion: Spiritual management effectively enhances nurses’ competence and patients’ well-being in palliative care. Recommendation: Integration of spiritual management into nursing practice and further studies with larger samples and longer durations are recommended.